Diagnostic Value of Cyclooxygenase-2 Serum Levels in Predicting Preterm Labor - Suhandri, Wiwin; Djanas, Dovy (Fakultas Kedokteran Universitas Andalas, 2020)
Objective: To determine the value of serum cyclooxygenase 2 in predicting preterm laborMethod: Examination of serum COX-2 levels by ELISA method in pregnant women with 28 weeks to 36 weeks of pregnancy compared with pregnant women with ≥37 weeks of gestation at the time of first stage of active phaseResults: It is known that the average COX-2 level in preterm labor is 21.88 ± 18.22 higher than in term labor which is 4.88 ± 2.35 ng / ml, the statistical test results obtained p = <0.001 serum Cyclooxygenase 2 at preterm deliveries and term deliveries. The value of serum cyclooxygenase 2 levels in predicting preterm labor is at a cut point of 7.0.0 ng / ml with a sensitivity of 86.1% and a specificity of 86.1%Conclusion: There were significant differences in serum cyclooxygenase 2 levels in preterm labor and term delivery Keywords: cyclooxygenase 2, memprediksi persalinan preterm, persalinan preterm.